Raziskovalni trendi in trajnostne rešitve v inženiringu poslovnih sistemov (University of Maribor Press, 2024)
Research Trends and Sustainable Solutions in Enterprise Engineering. In an effort to create a sustainably efficient, successful, and stable business environment, organizational leaders rely heavily on knowledge of appropriate approaches, methods, and techniques to assist them in selecting appropriate actions to achieve desired outcomes. To this end, in this monograph, the authors present research trends and sustainable solutions in enterprise engineering that provide additional support to organizations in achieving their goals. Managing innovation, optimizing maintenance, incorporating proactive ergonomics, managing business process efficiency and effectiveness, and organizational change, as well as managing sustainable supply chains, are just a few of the challenges that managers in organizations need to pay more attention to in order to create a more sustainable future. In addition to the theoretical presentation of trends and the application of individual approaches, individual examples from practice are also presented.